Mensuração e controle dos custos na cadeia interna de valor: um estudo de caso na suinocultura da região norte de Mato Grosso - Sornberger, Geovane Paulo (Universidade Federal de São Carlos, 2010)
The objective of this study was to propose systematic processes to measure and control costs of the Complete Production Cycle in a pork carcass manufacturer. Such processes will evidence the contribution of each internal value chain activity towards the generation of economic result. The methodology used includes a qualitative research and a case study. In addition to the literature review, the data were collected according to the following steps: (i) mapping the productive process in loco, which was considered the direct observation phase; (ii) semi-structured interviews with decision makers and those responsible for value activities; and (iii) documentary research through the analysis of internal documents. Based on the understanding of how the activities manage and use the resources, it was possible to develop systematic processes that enable cost analysis and the assessment of the contribution of each value activity towards the creation of operating results in the company. Those systematic processes can assist decision makers through different analyses of the company s internal value chain allowing comparisons with services provided by competitors. In general, it can be said that the adoption of the systematic processes proposed allows continuous assessment of all value activities of the company ensuring adequate and proper decision making.
Keywords: Controle de custo; Análise de valor (Controle de custo); Gestão estratégica de custos; Suíno - criação; Gestão de custos; Cadeia de valor; Suinocultura; Cost management; Value chain; Pig farming; ENGENHARIAS::ENGENHARIA DE PRODUCAO